2015
DOI: 10.1097/aln.0000000000000774
|View full text |Cite
|
Sign up to set email alerts
|

Novel 10-kHz High-frequency Therapy (HF10 Therapy) Is Superior to Traditional Low-frequency Spinal Cord Stimulation for the Treatment of Chronic Back and Leg Pain

Abstract: HF10 therapy promises to substantially impact the management of back and leg pain with broad applicability to patients, physicians, and payers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
720
2
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 733 publications
(782 citation statements)
references
References 22 publications
44
720
2
16
Order By: Relevance
“…These reports also suggest equivalent pain relief is achievable with 10 kHz and lower rates (either 1 or 2 kHz), but using in‐clinic pain scores they observed 70–80% improvement from baseline. These findings are also consistent with the SENZA RCT 1 which assessed back pain VAS in the clinic and reported 62.8% mean VAS change from baseline, while also assessing back pain (at rest) via paper diary and reported 56.2% reduction 50. Similarly, the SENZA RCT responder rate based on in‐clinic assessment of pain (78.4%) was greater than the responder rate based on paper diary (65.7%) 50.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These reports also suggest equivalent pain relief is achievable with 10 kHz and lower rates (either 1 or 2 kHz), but using in‐clinic pain scores they observed 70–80% improvement from baseline. These findings are also consistent with the SENZA RCT 1 which assessed back pain VAS in the clinic and reported 62.8% mean VAS change from baseline, while also assessing back pain (at rest) via paper diary and reported 56.2% reduction 50. Similarly, the SENZA RCT responder rate based on in‐clinic assessment of pain (78.4%) was greater than the responder rate based on paper diary (65.7%) 50.…”
Section: Discussionsupporting
confidence: 85%
“…SENZA did report a larger NRS decrease (∼70%) 1 than the ED‐NRS decrease (∼50%) reported by PROCO, but this difference is likely explained by the different methods used in each study to measure pain (see Discussion section Direct comparison of pain assessment using e‐diary with pain assessment in the clinic ). Also, patients and clinicians in the SENZA RCT knew which treatment was being applied, and multiple studies have shown that positive and negative patient expectations can significantly impact pain, sleep, depression, and physical function 53, 54, 55, 56.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Detailed methods, including subject demographics and subject flow diagram, are described elsewhere [29]. Briefly, a pair of percutaneous leads was placed in the dorsal epidural space along the radiographic midline of the spinal column and stimulation was trialed for up to 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…Device-related FDA approvals have been performed largely by the acquisition of level 1 data, regarded as the most robust and scientifically valid evidence available [4][5][6]. Understandably, it is the foremost position of the FDA to approve products that have proven efficacy and safety and to protect the public while allowing access to the best care possible and innovation.…”
Section: The Drg Storymentioning
confidence: 99%